MEMERANKAN MEDIA SOSIAL SEBAGAI MEDIA DAKWAH DALAM MEMINIMALISASI GERAKAN RADIKAL - Moh Rosyid (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2019)
This paper aims at proposing an alternative perspective on social media. While social media is sometimes used to disseminate radicalism and terrorism, it is actually providing a space for delivering a modest, peaceful, and humanistic religious teaching. Data to be analysed, in descriptive qualitative method, are collected from social media broadcast. Hopefully it will spread awareness that social media can a tool to counter radicalism. Thus, mutual understading need to be strengthened among the government, society and religious leaders concerning the use of social media to promote peace and harmony.